Cellular Automata and Discrete Complex Systems : 20th International Workshop, AUTOMATA 2014, Himeji, Japan, July 7-9, 2014, Revised Selected Papers - Isokawa, Teijiro; Imai, Katsunobu; Matsui, Nobuyuki; Peper, Ferdinand; Umeo, Hiroshi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes revised selected papers from the 20th International Workshop on Cellular Automata and Discrete Complex Systems, AUTOMATA 2014, held in Himeji, Japan, in July 2014. The 10 regular papers included in this volume were carefully reviewed and selected from a total of 25 submissions. It also contains one invited talk in full paper length.
Complexity of One-Way Cellular Automata -- Computational Complexity of the Avalanche Problem on One Dimensional Kadanoff Sandpiles -- 5-State Rotation-Symmetric Number-Conserving Cellular Automata are not Strongly Universal -- A Universal Cellular Automaton Without Sensitive Subsystems -- Real-Time Reversible One-Way Cellular Automata -- Cycle Equivalence of Finite Dynamical Systems Containing Symmetries -- Generalized FSSP on Hexagonal Tiling: Towards Arbitrary Regular Spaces -- Strict Majority Bootstrap Percolation on Augmented Tori and Random Regular Graphs: Experimental Results -- Rapaport Language Recognition by Reversible Partitioned Cellular Automata -- Complexity of Conjugacy, Factoring and Embedding for Countable Sofic Shifts of Rank 2 -- Plane-Walking Automata.
Keywords: Computer science; Computer software; Computer simulation; Computer Communication Networks; Data structures (Computer scienc; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Simulation and Modeling; Computer Communication Networks; Data Structures